Assessing optimal dispatch and pool market (symmetric and asymmetric) results for different periods - Henrique Evora (U.Porto Journal of Engineering, 2024)
This document presents a solution for an assignment related to the Energy Markets and Regulation curricular unit of PDEEC. The assignment consists of assessing optimal dispatch and pool market (symmetric and asymmetric) results for different periods. To check the technical feasibility of implementing the dispatch recommended by the pool market, a DC power flow is analyzed, by accounting for a network with six busbars. Results show that in some periods of higher demand, there could be an overload in some transmission lines of the considered network for certain results of market dispatch.